Non-polio enterovirus species c infection in AFP cases and its implication for the emergence of recombinant circulating vaccine- derived polioviruses (2020)
Using 40 faecal samples from acute flaccid paralysis (AFP) cases collected in 2019, we examined how coupling Enterovirus (EV) isolation in RD and MCF-7 cell culture with direct detection from clinical sample might impact our ability to detect non-polio EV Species C (NPESC) members in stool samples. In all, 20% (8/40) of all the samples screened had NPESCs and 50% (8/16) of the EVs detected were NPESCs. However, the RD cell line missed all NPESCs. Hence, RD cell line alone should not be used for EV isolation if the desire is to also isolate NPESC.